2015
DOI: 10.1016/j.ijdrr.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The current cyclone early warning system in Bangladesh: Providers' and receivers' views

Abstract: Bangladesh has experienced several catastrophic Tropical Cyclones (TCs) during the last decades. Despite the efforts of disaster management organizations, as well as the Bangladesh Meteorological Department (BMD), there were lapses in the residents' evacuation behavior. To examine the processes of TC forecasting and warning at BMD and to understand the reasons for residents' reluctance to evacuate after a cyclone warning, we conducted an individual in-depth interview among the meteorologists at BMD, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 42 publications
0
46
0
Order By: Relevance
“…Survey data from two Bangladeshi islands show that around 98 % of residents have trust in the early warning system (Paul and Rahman, 2006). More recently a survey of 200 households in coastal areas affected by Cyclone Sidr in 2007 and the less severe Cyclone Mahasen in 2013 found that 90.5 % of the 200 respondents received warnings during Sidr, and this number increased to 96 % during Mahasen (Roy and Kovordanyi, 2015;. It also found that 83 % of the respondents claimed the warnings to be understandable .…”
Section: Discussionmentioning
confidence: 99%
“…Survey data from two Bangladeshi islands show that around 98 % of residents have trust in the early warning system (Paul and Rahman, 2006). More recently a survey of 200 households in coastal areas affected by Cyclone Sidr in 2007 and the less severe Cyclone Mahasen in 2013 found that 90.5 % of the 200 respondents received warnings during Sidr, and this number increased to 96 % during Mahasen (Roy and Kovordanyi, 2015;. It also found that 83 % of the respondents claimed the warnings to be understandable .…”
Section: Discussionmentioning
confidence: 99%
“…Without vulnerable condition natural hazard will not appear as disaster. In this case defensible capacity building of community as well as long-term preparedness and effective early warning system are very crucial for reducing the losses of lives and property (Roy et al 2015). Therefore, an attempt has been made in this study to examine the effectiveness of disaster mitigation measures undertaken by individuals, GOs and NGOs to minimize the impacts of cyclones in the coastal areas of Bangladesh.…”
Section: _####_ Page 2 Of 11mentioning
confidence: 99%
“…Similarly, Hoque et al (2018) depicts the risks of the cyclone for present and future climate change scenarios using geospatial techniques. Correspondingly, a number of papers also have been written focusing community response and coping strategies (Paul and Routray 2010;Islam et al 2017), influencing factors (Hossain 2015), cyclone forecast and warning dissemination (Roy et al 2015) and preparedness aspects of cyclone disaster (Mallick and Vogt 2013). Although many studies have been conducted in Bangladesh on cyclones but the thorough and exhaustive study on the role of vulnerability factors and effectiveness of disaster mitigation measures in coastal Bangladesh is just about limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Roy, C., Sarkar, S. K., Åberg, J., & Kovordanyi, R. (2015). The current cyclone early warning system in Bangladesh: Providers' and receivers ' views.…”
Section: Studies Conducted In This Researchmentioning
confidence: 99%
“…First study: Evaluation of the efficiency of a cyclone early warning system. The primary goal of this study was to elicit the views both of the meteorologists at the Bangladesh Meteorological Department (BMD) and of the residents in the coastal areas of Bangladesh on the current cyclone early warning system in Bangladesh.Research article published on the basis of the findings of this study:• Roy, C., Sarkar, S. K., Åberg, J., & Kovordanyi, R. (2015). The current cyclone early warning system in Bangladesh: Providers' and receivers' views.…”
mentioning
confidence: 99%